Experimental and variational-based analytical investigation of multiple cracked angle-ply laminates. (1st March 2018) - Mohammadi, Bijan; Pakdel, Hamed
Highlights: Angle-ply laminated composites with different layup may form mid or outer-ply matrix cracks. Ply refinement technique improves stress state and mechanical properties of the cracked laminate. All matrix crack patterns are considered to predict mechanical properties of cracked laminates. Cracked laminate stresses show that cracks propagate with a pattern similar to initiation pattern. Abstract: A unit cell based method is developed based on variational principles to derive the stress state and effective mechanical properties of angle-ply laminates of type [ θ m ( o ) / θ n ( i ) ] s containing whether mid-ply or outer-ply matrix cracks positioning in a symmetric or staggered pattern through the laminate. All plausible matrix crack distribution patterns are considered and implementing the principle of minimum complementary energy, an admissible stress field is derived. For the first time effects of ply refinement technique, layup configuration and crack distribution pattern on the stress state and degradation of mechanical properties of angle-ply laminates are investigated and compared to finite element results. CFRP test specimens are prepared and optical microscopy is utilized to detect matrix crack densities during tensile tests. Obtained analytical stiffness reductions for different crack densities are confirmed to be in agreement with experimental observations.